EFFECTIVENESS OF ARTICLE 27(1) OF LAW NUMBER 1 OF 2024 IN COMBATING ONLINE INDECENCY (CRIMINOLOGICAL PERSPECTIVE) - Hurairah; Timur, Widya; Royani, Ferawati; Aprianto, Sandi (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
The rise of immoral criminal acts on social media, such as the dissemination of nudity content and various other types of cyberporn raises serious concerns regarding social and legal impacts. This study aims to analyze the effectiveness of Article 27 paragraph (1) of Law Number 1 Year 2024 on Electronic Information and Transactions (ITE Law) in dealing with the rise of indecent criminal acts on social media using an in-depth criminology theory analysis. This research uses the normative empirical method, which examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on each specific legal event that occurs in society. The results of this study show that the Differential Association criminology theory can explain how immoral criminal acts develop on social media. This theory argues that deviant behavior can be learned through social interaction with groups that support deviant norms. Meanwhile, although the ITE Law is an important step in law enforcement efforts, its implementation still needs to be improved so that it can be more effective in overcoming the spread of immoral content on social media. Keywords: Indecent Crime, Social.